Active control for adaptive origami structures undergoing damage. (1st September 2021) - Sychterz, Ann C.; Baruah, Angshuman C.
Highlights: Form-finding analysis developed for origami structure to include folding and bending stiffness. Sensitivity analysis using potential energy successfully rank damage risk of elements and best measurement locations on structure. Comparison of measured and simulated origami actuation successfully characterize rigid (folding) and non-rigid (curling) actuation movements. Using changes in natural frequencies for successful detection of damaged elements. Abstract: Origami structures, such as those with a Miura-Ori fold pattern, have one principle direction of kinematic freedom where rigid foldability holds true. However, motions such as twisting and curling, and bending require that origami panels bend, thus adding complexity to the system. The goal of this work is to study the actuation of Miura-Ori structures for damage detection. The combination of form-finding for large displacements and finite element model for dynamic characterization is successful to capture the kinematic properties of the Miura-Ori origami structure movements of folding and curling. Simulations and experimental tests are useful as a starting point for determining the behavior of mid-scale actuated origami structures. Stiffness values for folding of creases and bending of panels must be considered when modeling shape change of Miura-Ori origami structures using dynamic relaxation. Energy produced by the folding and bending stiffness values activated in the structure through actuation is a useful measure to rank elements in terms of their potential for damage.